The influence of plural governance systems on rural coastal livelihoods: the case of Kosi Bay - Mbatha, Nonhlanhla Philile (Department of Environmental and Geographical Science, 2019)
Thousands of rural households along the South African coast rely on fisheries resources, forest products and agricultural resources in order to support their livelihoods. These customary livelihoods have continued in many rural areas despite restrictive policies and laws during the colonial and apartheid administrations. More contemporary restrictions have emerged in the post-1994 democratic state due to an expansion of the conservation estate and increased efforts to improve compliance in existing protected areas. This conservation drive is due largely to environmental concerns as well as the country’s international and national commitments to enhance biodiversity protection. Statutory conservation governance in rural areas in South Africa often operates in parallel to traditional and customary systems of governance. This results in confusion and conflict emanating from the plurality of governance systems, actors and institutions whose powers, roles and approaches are informed by different norms, discourses, values, images and worldviews. This study seeks to enhance understanding about the conceptual linkages between livelihoods and plural governance systems, using the case study of Kosi Bay, a coastal region in northern KwaZulu-Natal, South Africa. This was done using a case study methodology and empirical research to: a) describe livelihood strategies; b) identify and document statutory, traditional and customary governance structures linked to coastal resource governance; c) explore the norms, discourses, images, values and worldviews that have informed coastal resource governance in this area; d) review and analyse the influences of plural coastal governance systems on livelihood strategies; e) contribute towards conceptual frameworks that link livelihoods and governance and; f) make recommendations for improved livelihoods and governance in rural areas in the South African context and beyond. The study underscores the manner in which legal pluralism and historical context affect and influence governance processes, and demonstrates that the day-to-day livelihoods of rural people are diverse and dynamic, and can be profoundly affected by meta-level and institutional governance processes and practices. It concludes by highlighting the manner in which legal pluralism and historical context significantly affect and influence governance processes that shape rural livelihoods, and provides a set of recommendations for consideration.